Pertahanan Ekonomi: Menelusuri Hubungan antara Anggaran Pertahanan, Impor Alutsista, dan Kurs di Lima Negara ASEAN - Talhis Alif; Rizka Jafar (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The strength of a country can be measured through two elements, namely the military and the economy by looking at the aspect of the country's economic growth. National defense is not only useful for military needs, but also helps economic growth. Keynes stated that national defense is part of a public good so that if the country is defended, then someone will enjoy the benefits it gets. The purpose of this study is to compare and examine the effect of military and economic indicators on the country's economic growth rate. The study was conducted in five ASEAN countries, namely Indonesia, Malaysia, Singapore, the Philippines and Thailand using secondary data obtained by the World Bank from 2009 to 2020. This research method uses panel regression with fixed effect model testing. The results show that the defense budget and the exchange rate have a significant positive effect on economic growth, whereas imports of defense equipment have a significant negative effect on economic growth.